2021
DOI: 10.1177/13621688211024364
|View full text |Cite
|
Sign up to set email alerts
|

Seeing or acting? The effect of performing gestures on foreign language vocabulary learning

Abstract: We evaluate the impact of gestures during the teaching of vocabulary in a foreign language (FL). Spanish speakers learned words in a FL in four gesture conditions according to the relationship between the meaning of the words and the gestures (congruent gestures, incongruent gestures, gestures without meaning, and no gestures). The participants learned the words by performing gestures (‘do’ teaching group) or by observing the gestures performed by others (‘see’ teaching group). Compared to the meaningless gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Differences appeared between incongruent and meaningless gestures but similar results were obtained when the congruent and no-gesture conditions were compared (see Figure 8). Extended information about statistical data is provided in the paper published by García-Gámez and Macizo in 2021 [4].…”
Section: Results Of Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences appeared between incongruent and meaningless gestures but similar results were obtained when the congruent and no-gesture conditions were compared (see Figure 8). Extended information about statistical data is provided in the paper published by García-Gámez and Macizo in 2021 [4].…”
Section: Results Of Experimentsmentioning
confidence: 99%
“…Due to the global and multicultural ambiance we are involved in nowadays, it is mandatory to be able to communicate in different languages. Early techniques for acquiring foreign language (FL) vocabulary employed a first language (L1)-FL word association strategy aimed at establishing connections between newly acquired FL words and their corresponding lexical translations in the native language [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Imitation involved the observation and execution of other's actions (Tellier, 2008;Mainieri et al, 2013;García-Gámez et al, 2021), which can not only provide semantic information but also activate students' motor and perception systems, thus affecting the cognitive process (James & Swain, 2011;García-Gámez et al, 2021). Embodied cognition theory provided explanations for the positive effects of imitating the instructors' depictive gestures (Wilson, 2002).…”
Section: Comparisons Of Observation Imagination and Imitation Strategiesmentioning
confidence: 99%
“…As a passive learning strategy, observing gestures did not always guarantee the effectiveness of learning (Pi et al, 2019;Brucker et al, 2022). Additionally, studies have shown that compared to the observation strategy, the two active strategies of imagination and imitation take advantage of the instructor's depictive gestures (Baills et al, 2018;García-Gámez et al, 2021;Leopold et al, 2019). Imagination is an effective generative learning strategy, helping students construct mental imagery, but increasing the cognitive load (Leahy & Sweller, 2004;Fiorella & Mayer, 2015;Leopold et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation